1995
DOI: 10.1126/science.270.5236.625
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Arc Geochemical Variations in the Kurile Arc as a Function of Slab Depth

Abstract: Lavas from transects across the Kurile Islands arc showed geochemical variations related to changes in the compositions of fluids derived from the subducting slab. Enrichment factors for boron, cesium, arsenic, and antimony, all elements with strong affinities for water, decreased across the arc. This decrease is presumably related to losses of water-rich fluids during the dehydration of the subducting plate. Enrichments of potassium, barium, beryllium-10, and the light rare earth elements remained constant; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
116
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(132 citation statements)
references
References 31 publications
13
116
0
3
Order By: Relevance
“…The enrichment of EVF and CKD melt inclusions in U, Th, K, Ba, La, Pb and the positive correlation of these elements with B suggests that the B-rich fluid also carries these elements. Our melt inclusion data are in agreement with previously published results (Ryan et al 1995;Ishikawa and Tera 1997;Ishikawa et al 2001; Wörner et al Dy / Yb 2 2001), suggesting that B-rich fluids are contributed in EVF and CKD regions. In detail, however, a significant difference in fluid compositions is observed between EVF-and CKD-fluids.…”
Section: Sulfur Chlorine and Fluid-mobile Elementssupporting
confidence: 83%
See 2 more Smart Citations
“…The enrichment of EVF and CKD melt inclusions in U, Th, K, Ba, La, Pb and the positive correlation of these elements with B suggests that the B-rich fluid also carries these elements. Our melt inclusion data are in agreement with previously published results (Ryan et al 1995;Ishikawa and Tera 1997;Ishikawa et al 2001; Wörner et al Dy / Yb 2 2001), suggesting that B-rich fluids are contributed in EVF and CKD regions. In detail, however, a significant difference in fluid compositions is observed between EVF-and CKD-fluids.…”
Section: Sulfur Chlorine and Fluid-mobile Elementssupporting
confidence: 83%
“…13b; Ryan et al 1995;Wörner et al 2001;Ishikawa et al 2001) and the role of a Li-rich fluid increases, the Li/B ratio shows a strong cross-arc zonation (Fig. 13c).…”
Section: Li-b Decoupling Across the Kamchatka Arcmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the ratio of FME to FIE in volcanic rocks decreases continuously from the volcanic front to the back-arc side (46,47). These across-arc geochemical variations have often been interpreted as a sign that the amount of fluid released from a slab decreases continuously with increasing depth of the Wadati-Benioff zone, assuming that the trace element composition of the fluid remains constant with slab depth (46).…”
Section: Depths Of the Second Critical Endpoints And Their Bearing Onmentioning
confidence: 99%
“…High boron abundance in volcanic front lavas decreases across the arc (Ryan et al, 1995;Ishikawa and Tera, 1997;Miyoshi et al, 2008). The continuous depletion of boron reflects the gradual depletion of volatiles and fluid-mobile elements during dehydration of the subducting slab (Ishikawa and Tera, 1997).…”
Section: Along-arc Variations Of Boron and Other Predominately Slab-dmentioning
confidence: 99%